Análise microbiológica da exposição das roscas dos implantes osseointegráveis no seio maxilar de ovelhas - Gaujac, Cristiano [UNESP] (2014)
Aim - The purpose of this study is to evaluate the microbiological changes with exposure expiras of dental implants in the maxillary sinus. Materials and methods - The experiment goes through two stages where eight sheep were used. In the first phase swabs were performed in the maxillary sinuses for pathway extra orally immediately followed by the placement of an implant in each maxillary sinus via the same pathway. On the right side the implant had the treated surface and the left surface has been machined. In the second stage, performed three months after the first, the in the mucosa swab was redone and a smear was performed at the implant surface with a sterile microbrush. The culture media used were blood agar, chocolate agar, MacConkey, mannitol salt agar and Sabouraud agar. Statistical analysis was performed using the Student t test, Fisher and Binomial. Results - In the first stage of the study showed 37.5% of breasts with positive growth rising to 50% in the second stage and 80% of the placed implants colonized by microorganisms. Three months after implant placement has been a proliferation of Staphylococcus aureus and significant growth of yeasts (student t test, p = 0.0413) with significant edema of the mucosa of the maxillary sinus despite not presenting any clinical signs of infection, two machined implants do not osseointegraram. There was no significant difference between the machined surface implants and treated with the colonization of microorganisms. Conclusion - Exposure of implants to the maxillary sinus provides a proliferation of Staphylococcus aureus and fungi and there was no difference between the treated surface machined in the colonization of microorganisms implants.